Advance of Nano-Composite Electrospun Fibers in Periodontal Regeneration - Zhuang, Yu; Lin, Kaili; Yu, Hongbo (Frontiers in Chemistry, 2019)
Periodontitis is considered as the main cause of tooth loss, which influences about 15% of the adult population around the world. Scaling and root-planning are the conventional treatments utilized to remove the contaminated tissue and bacteria, but finally lead to the formation of a poor connection - long junctional epithelium. Therefore, regenerative therapies, such as guided tissue/bone regeneration (GTR/GBR) for periodontal regeneration have been attempted. In which, GTR membranes, acting as scaffolds, create three-dimensional (3D) environment for the guiding of cell attachment, proliferation and differentiation, and play a significant role in periodontal regeneration. Nano-composite scaffolds based on electrospun nanofibers have gained great attention due to their ability to emulate natural extracellular matrix (ECM) that affects cell survival, attachment and reorganization. Promoted protein absorption, cellular reactions, activation of specific gene expression and intracellular signaling, and high surface area to volume ratio are also important properties of nanofibrous scaffolds. Moreover, several bioactive components such as bioceramics, functional polymers can be easily blended into nanofibrous matrixes to regulate the physical-chemical-biological properties and regeneration abilities. Simultaneously, functional growth factors, proteins and drugs are also incorporated to regulate cellular reactions and even modify the local inflammatory microenvironment, which benefit periodontal regeneration and functional restoration. Herein, the progress of nano-composite electrospun fibers for periodontal regeneration is reviewed, including fabrication methods, compound types and processes, and surface modifications, etc. Significant proof-of-concept examples are utilized to illustrate the results of material characteristics, cellular interactions and periodontal regenerations. Finally, the existing limitations of nano-composite electrospun fibers and the development tendencies in future are also discussed.